Mining Crisis and National Strike,1925/26 - Copies of all Reports (page 2)
1926-12-31 "Mining Crisis and National Strike,1925/26 - Copies of all Reports (page 2)" [g0488002.jpg], 1925/26, Miners' Federation of Great Britain